Propiedades magnéticas de los sedimentos de tipo estuarino. El caso de las Rías Baixas. - Pazos, O.; Bógalo, M.F.; Rey, D.; Rubio, B.; Vilas, Federico; López-rodríguez, N.; Mohamed, K. (Journal of Iberian Geology, 2000)
Meassurement of magnetic susceptibility has allowed the assesment of the marine influence and diagenetic evolution of coastal sediments from the Rías Baixas. This is based on geographically and vertically distributed data. The lowfield susceptibility () of over 200 samples of surficial seabed sediments of the Rias of Vigo and Pontevedra showed a significant increase towards the open sea and away from continental influenced areas. Vertical variability of the susceptibility was evaluated in 80 samples obtained from three 60 to 90 cm long gravity corers in the Ria de Pontevedra. These samples showed a very strong decrease in susceptibility with depth. The surficial susceptibility values correlated well with the textural characteristics of the sediments, suggesting a link between sediment provenance and origin of the magnetic signal. To further evaluate these relationships, the available sedimentological data were completed with a number of elemental and mineralogical analysis. In addition some basic magnetic parameters were obtained for selected specimens. The combined analysis of these data showed that the spatial variability of the susceptibility observed in the different granulometric fractions can be spatially related to: (a) sediment provenance and origin, (b) hydrodynamic regime established between the Rias and the adjacent shelf, (c) antropogenic solid particulate pollution. It can also be concluded that the evolution of the magnetomineralogical phases during the early stages of burial and diagenesis is controlled by the organic matter content which in turn controls the redox potential.